The Concept of Islamic Musyawarah - Dedi Masri (Budapest International Research and Critics University, 2021)
Deliberation is a way of dealing with many problems that cannot only be resolved personally. As humans or as a society, we need to get involved with other people in solving the problems at hand, especially if the issue concerns the interests of the general public. For this reason, the involvement of other people is important so that the interests of others are also accommodated or accommodated in the decisions that are taken. Western nations call it a democracy that makes humans as the owner of the highest authority, while deliberation in Islam is the way that Allah SWT has given as the sole decision maker. Deliberation is the key word in various issues to avoid conflict. For Muslims, accepting the principle of deliberation to build consensus is a matter of aqidah.